(untitled) (LIS TODAY, 2022)
The way and circumstances have changed in the COVID-19 era. It is why effective and reliable online library services has become essential for every library, but providing online services especially for small libraries is relatively difficult and blogs have emerged as an effective tool for online services by small libraries. The present paper explores the concept, types of blogs, some of the major open source blogging tools and its utility in library services